Phonemic Harmony in Sufi Discourse - Said, Hamza (Milev Journal of Research and Studies, 2022)
This paper aims to study the expressive values of linguistic sounds. This latter does not indicate meanings, but expresses emotions and suggesting meanings. This is what the recipient realizes with his phonetic intuition and knowledge of Arabic sounds and their characteristics through being able to build the harmony that occurs between the outputs of the sounds, their qualities and the meanings expressed. Different authentic or correct sounds (consonants and vowels) reflecting word expressions and long vowels then their appliance on some sample descriptive texts are studied. Concluding with a number of results, the most important of which is that the receiver is the one who builds the vocal harmony, and in this case, the relationship of sound with meaning is not arbitrary. Use of Times New Roman font in the title, size 10, bold, interline spacing 1, and font type in Times New Roman text, size 10, interline spacing 1,15 (this format applies to words keys). The summary is followed by keywords as cited in the article taking into account not to exceed 5 keywords.